Place of Error Correction in English Language Teaching - Ali Akbar Khansir; Farhad Pakdel (Educational Process: International Journal, 2018)
This review paper is intended to discuss the function, objective and aim of correction as a language strategy in English language learning. In reality, correction is termed as feedback by teachers. Feedback is useful where there is a lack of knowledge, especially the failure of students to use language correctly. Error correction is not an essay and it is should be practiced as instructed by the teacher in a language teaching setting. Error correction is a way to develop competence of language learners in a second or foreign language. It can be used in order to attain conscious knowledge of a second or foreign language, and in learning the language’s rules. What is important is that errors in language speech and writing are viewed as having detrimental effects when acquiring a second or foreign language.